Replacement of fish meal in cobia, Rachycentron canadum (Linnaeus, 1766) diets using poultry by-product and feather meal - Saadiah Ibrahim (Institut Akuakultur Tropika, 2012)
An 8-week feeding trial was conducted to evaluate the use of local poultry by-product meal (PBM) in replacement of imported fish meal in the diets of cobia. Eleven juvenile cobia fish (30.7 ± 0.78 g) were randomly stocked in 300-L circular fibreglass tanks and hand-fed based on the total biomass of each tank, twice a day at 0900 h and 1500 h.